Reduction of radiation transmission through functionalization of textiles from man-made cellulosic fibers - Kristina Klinkhammer; Karin Ratovo; Oliver Heß; Ellen Bendt; Thomas Grethe; Marcus Krieg; Michael Sturm; Thomas Weide; Boris Mahltig (Communications in Development and Assembling of Textile Products)
Both ultraviolet (UV) and infrared (IR) light have negative impact on the human health. With this background it is the main aim of the current research to realize a textile material which is able to protect against both UV light and IR light. For this research, regenerated cellulosic fibers from the Lyocell process are used and modified. Main analytical investigations are done by photo-spectroscopy in arrangement of diffuse transmission for the spectral range from 220 nm to 1400 nm. Additionally, microscopic investigations are done by scanning electron microscopy (SEM). For material development, Lyocell fibers functionalized with TiO2 particles are first processed into yarns and then into knitted fabrics. Compared to non-functionalized textiles, the transmission is reduced in the UV range due to the absorption behavior of TiO2. Subsequent dyeing with anthraquinone or reactive dyes enhanced the UV protective effect. To reduce the transmission in the near IR range (NIR), non-functionalized Lyocell knitted fabrics are functionalized with various IR absorbers in different concentrations. With increasing concentration, the transmission decreased. However, a grey coloration of the textile is observed simultaneously, with increased concentration. This must be considered in further processing steps. With these methods for functionalization, it is possible to produce textiles that offer increased protection against UV and IR radiation. These are promising materials for the production of clothing or work wear.